2018
DOI: 10.1080/15476286.2018.1486659
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of circular RNAs in cancer development and progression

Abstract: Circular RNAs (circRNAs) are a large class of endogenously expressed non-coding RNAs formed by covalently closed loops through back-splicing. High throughput sequencing technologies have identified thousands of circRNAs with high sequence conservation and cell type specific expression in eukaryotes. CircRNAs play multiple important roles in cellular physiology functioning as miRNA sponges, transcriptional regulators, RBP binding molecules, templates for protein translation, and immune regulators. In a clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
129
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(131 citation statements)
references
References 117 publications
2
129
0
Order By: Relevance
“…In recent years, the role of circRNAs in oncogenesis and cancer progression has caused wide attention. Due to cell/tissue-specific and stage-specific expression and unique molecular structure, circRNAs might have regulatory functions in many biological processes and are better diagnostic markers or therapeutic targets for cancer than linear transcripts [23]. However, the expression and role of most circRNAs in TNBC development are still largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the role of circRNAs in oncogenesis and cancer progression has caused wide attention. Due to cell/tissue-specific and stage-specific expression and unique molecular structure, circRNAs might have regulatory functions in many biological processes and are better diagnostic markers or therapeutic targets for cancer than linear transcripts [23]. However, the expression and role of most circRNAs in TNBC development are still largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,8,13,18,19 Recent studies have confirmed that circRNA is involved in the regulation of gene expression by various means, thereby indirectly participating in the occurrence and development of various solid cancers. 6,[9][10][11]13,14,16,17 However, the biological functions of circRNA in BC are scarcely reported. In this study, we investigated the expression of hsa_circ_0068033 expression in BC tissues and cell lines and explored the influence of overexpressed hsa_circ_0068033 on the biological characteristics of MCF-7 and MDA-MB-231.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In addition, circRNA can directly bind to proteins, or establish an indirect RNA-mediated association with proteins to influence their functions. 8 Studies have reported that circRNA is closely correlated with the occurrence and development of various malignant tumors, including liver cancer, 9,10 lung cancer, 11,12 cervical cancer 13 gastric cancer, 14,15 colorectal cancer, 16,17 etc. In recent years, the potential applications of circRNA in the regulation of biological functions and the clinical diagnosis and prognosis of BC have received considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…CircRNA, a class of enclosed non-coding RNA molecules generated by RNA splicing, function as an miRNA sponge and regulate gene transcription and alternative splicing [18,19,8,13,4,5]. Recent studies have confirmed that circRNA is involved in the regulation of gene expression by various means, thereby indirectly participating in the occurrence and development of various solid cancers [13,11,10,6,17,9,16,14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, circRNA can directly bind to proteins, or establish an indirect RNA-mediated association with proteins to influence their functions [8]. Studies have reported that circRNA is closely correlated with the occurrence and development of various malignant tumors, including liver cancer [9,10], lung cancer [11,12], cervical cancer [13] gastric cancer [14,15], colorectal cancer [16,17], etc. In recent years, the potential applications of circRNA in the regulation of biological functions and the clinical diagnosis and prognosis of BC have received considerable attention.…”
Section: Introductionmentioning
confidence: 99%